Avaliação de uma proposta didática sobre força e movimento referenciada na teoria de aprendizagem significativa : uma gincana de conhecimentos como principal recurso utilizado - Pereira, Vanessa de Oliveira (2016)
This study is a report of the application of an instructional material (IM) applying topics of kinematics and Newton's laws for the Bodies Movement. This research was conducted with two groups of 1st grade of high school students, in a state school in the city of Serra, in the state of Espírito Santo. The MI was created based on the theoretical aspects of Meaningful Learning of Ausubel, the Motivational Strategies proposed by Bzuneck and the guidelines for the development of Potentially Meaningful Teaching Unit of Moreira. As data collection instruments, were used concept maps, Pre- and Post-Test and Registration of Personal Notes of the teacher/master student on the application of MI. The design used in this work was the experimental and data analysis was performed under the qualitative and quantitative approaches, depending on the analyzed collection instrument. The results of the statistical tests showed that the MI prepared helped the performance improvement in the post-test of experimental group of students compared to the control group. The analysis of the Final Concept Maps, according to the methodology, found an improvement in all the quantitative criteria, as well as the qualitative criteria Map Quality. Analysis of the Personal Notes of the teacher/master student studies showed that the inclusion of situations experienced by students in their daily lives and in a contest that happened, were considered relevant to the teaching/learning of the discussed concepts. The results show evidence that MI contributed to promotion of learning of concepts related to the topics of Kinematics and Newton's laws for the Bodies Movement for high school students.